SOS in the mangrove ecosystem of Nazabal Beach in Encrucijada, Villa Clara, Cuba - García, José Javier Carrazana; Bacallao, Damaris Olivera; García, Rafael Armiñana; Pérez, George Argota; Castro, Oriali Fraga; Duarte, Rigoberto Fimia (Universitas Malikussaleh, 2025)
Climate change is an irrefutable reality that constitutes today, and in the future, one of the main threats affecting the survival of life on planet Earth. The objective of the research was to introduce the scientific result, social project: Monitoring the mangrove. The research was actually carried out in the village of Nazabal, Encrucijada, in the province of Villa Clara, Cuba. Fifteen students of the group of the twelfth-grade number 1 of the Urban Pre-University Institute